Perencanaan Strategis Sistem Dan Teknologi Informasi Pada PT Timur Jaya Panel Surabaya - Prasetyo, Nico; Sudarmaningtyas, Pantjawati; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
The main business process at PT Timur Jaya Panel are buying, selling, and marketing production goods. The problems faced by this company is the production, selling, buying, and marketing section are not integrated so redundancy of data and lost of linkage between information resourced caused by data spread is happened. The usage of different applocation causing data has to be included back to the main application. The other problem is that there’s no IT development direction so the company can’t difference between desires and needs. All of this caused by no IT strategic planning since 2008. Today this company needs IT strategic planning so the business strategy can be aligned with synchronizing company’s goals and IT goals. The IT strategic planning will give IT development direction for the next 3 years. The planning is designed by Anita Cassidy’s steps. The framework will include 4 steps which is visioning, analysis, direction, and recommendation. The results expected from this project is that this project will give IT direction for the next 3 years. The result will be realized with making IT direction so that the IT goals will be aligned with company’s business strategy by synchronizing company’s goals with IT goals.